2009
DOI: 10.1208/s12249-009-9287-1
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Lidocaine Lipid Nanosystems for Dermal Delivery

Abstract: The objective of the present investigation was to formulate solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) for improving the dermal delivery of a local anesthetic agent lidocaine (LID). SLN and NLC were characterized for particle size distribution, polydispersity index, entrapment efficiency, X-ray powder diffraction pattern (XRD), thermal behavior by differential scanning colorimeter (DSC) and surface morphology by transmission electron microscopy (TEM). LID-loaded SLN and NLC were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 23 publications
5
61
0
Order By: Relevance
“…The components of the NLC formulation have similar lipophilicity as the skin, so they have good miscibility with the skin lipids, and this can cause greater penetration [37]. Our results are in good agreement with other studies, which revealed that lipid nanocarriers can improve penetration and effectiveness of encapsulated lidocaine [2,5,38,39]. The high penetration rate of LID through the epidermis predicts the fast accumulation of the drug in the dermis, which is the site of action for local anesthetics.…”
Section: Results Of In Vitro Release and Ex Vivo Permeation Studiessupporting
confidence: 88%
“…The components of the NLC formulation have similar lipophilicity as the skin, so they have good miscibility with the skin lipids, and this can cause greater penetration [37]. Our results are in good agreement with other studies, which revealed that lipid nanocarriers can improve penetration and effectiveness of encapsulated lidocaine [2,5,38,39]. The high penetration rate of LID through the epidermis predicts the fast accumulation of the drug in the dermis, which is the site of action for local anesthetics.…”
Section: Results Of In Vitro Release and Ex Vivo Permeation Studiessupporting
confidence: 88%
“…The NLC formulation was evaluated for just 1 month in the above-mentioned conditions, and it was found to be stable. 49 Domperidone is a dopaminereceptor antagonist widely used in the treatment of motion sickness. Due to its poor water solubility and consequent low oral absorbability, extensive first pass metabolism which leads to poor oral bioavailability (around 15%), 50,51 therapeutic administration at low doses (10 mg) or for long-term treatment, and repetitive dosing make this drug an interesting candidate for the development of SLN and NLC.…”
Section: Impact Of Variables On Size Of Slns and Nlcsmentioning
confidence: 99%
“…The polydispersity index measures the width of the particle dispersion, providing information on the homogeneity of the particle size distribution of the system. The literature reports that polydispersity indices less than 0.3 are considered ideal and are referred to as indicating a narrow size distribution, 22,23 whereas polydispersity values less than 0.1 are referred to as monodispersed. 24 Therefore, according to Table 2, all the formulations had a narrow size dispersion.…”
Section: Particle Size and Zeta Potentialmentioning
confidence: 99%